2012
DOI: 10.1111/j.1440-169x.2011.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish enhancer trap line showing maternal and neural expression of kctd15a

Abstract: Potassium channel tetramerization domain containing proteins (KCTDs), which share a conserved BTB (Brica-brac, Tramtrack, Broad complex) domain at their N-terminus, are known to be involved in both developmental and neural processes. However, the developmental expression patterns and functional roles of most vertebrate KCTDs remain unknown. Using enhancer-trapping technology, we have identified a transgenic zebrafish line (ub49) where the vector insertion is in close proximity to kctd15a, and where transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(123 reference statements)
0
10
0
Order By: Relevance
“…As mentioned above, Kctd1 interacts with AP-2 (32,33). Kctd15, which we have shown to inhibit NC development and affect Wnt signaling and AP-2 function, is regulated by FGF in Xenopus, and an enhancer trap line that mimics kctd15 expression in zebrafish has been described (43,44). Further, the KCTD15 gene is associated with obesity in whole-genome association studies (53,54), but no molecular basis for such a link has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, Kctd1 interacts with AP-2 (32,33). Kctd15, which we have shown to inhibit NC development and affect Wnt signaling and AP-2 function, is regulated by FGF in Xenopus, and an enhancer trap line that mimics kctd15 expression in zebrafish has been described (43,44). Further, the KCTD15 gene is associated with obesity in whole-genome association studies (53,54), but no molecular basis for such a link has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be studied whether Kctd15 inhibits gene regulation by AP-2 in general or only in a certain context. Although the expression patterns of AP-2 and Kctd15 overlap in some regions, they show considerable differences (23,29,31,43,44), and thus not all AP-2 functions are likely to be affected by Kctd15.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the role of KCTD15 in human obesity may be associated with its ability to inhibit neural crest formation by interfering with Wnt/beta‐catenin signaling pathway upstream or in concert with β‐catenin . In zebrafish, the suppression of KCTD15 by morpholino technology leads to the expansion of the neural crest domain .…”
Section: Functional Evidence Indicates Possible Involvement Of Kctd15mentioning
confidence: 99%
“…Dorsal depletion of kctd15 in Xenopus embryos leads to bent axes with reduced head structures, defective eyes and abnormal somites, while ventral depletion causes defects in ventral and caudal morphologies . The zebrafish paralogue of KCTD15 , kctd15a, shows strong maternal expression suggesting a functional role during epiboly and gastrulation . At later stages, expression of kctd15a was observed in several neural tissues, including cranial placode precursors, different areas of the developing brain as well as in distinct cell populations within the retina .…”
Section: Functional Evidence Indicates Possible Involvement Of Kctd15mentioning
confidence: 99%
“…We found 6 of 9 predicted dorsal genes to be enriched in the dorsal mandibular and hyoid arches: cadherin11 (cdh11), pou3f3a and pou3f3b (homologs of mouse Pou3f3 with dorsal expression (Jeong et al, 2008)), cd248a, kctd15a (also see (Gharbi et al, 2012), and postnb ( Figure 2D). The other three genes were excluded from the dlx5a:GFP and hand2:GFP expression domains, as predicted, but they did not present typical "dorsal" expression patterns: sfrp2 showed dorsal-specific expression that failed to co-localize with dlx2a (likely dorsal arch mesoderm), rassf10a was largely confined to the surface ectoderm rather than arch CNCCs, and osr2 was expressed in only a few cells between the arches and the eye (Swartz et al, 2011).…”
Section: Dorsal Genesmentioning
confidence: 97%